High School Students' Affective Reaction to English Speaking Activities - Oliver Camilo Jorquera Torres; Jhon Eliot Mendoza Zapata; Claudio Heraldo Díaz Larenas (Asociación Colombiana de Profesores de Ingles, 2017)
This study aims to measure fifty-two high school students' affective reactions after doing individual and pair-based speaking activities then completing a semantic differential scale of nine bipolar adjectives. Results do not show significant statistical differences between the two types of activities or the schools involved in this study, but participants from both schools present a similar affective reaction towards individual and pair-based speaking activities.